Nutrition Management in COVID-19 Quarantine: Hospital-Based Study. (20th December 2023) - Tayyem, Reema; Al-Shudifat, Abdel-Ellah; Al-Alami, Zahra'; Abdelbaset, Mohammad G.; Al-Awwad, Narmeen; Azab, Mohammed
Abstract: Background: This hospital-based study aimed to evaluate the nutritional status and dietary habits, the amount of nutrients provided to the patients in the hospital and to detect the predictors of severity among COVID-19 patients in Jordan. Methods: A hospital-based study ( N = 367; mean age 42.3 y; SD 15.4; 66.0% men) was conducted between March 17 and July 25, 2020, in Prince Hamza Hospital. Data about socio-demographic, anthropometric, dietary habits, and macro- and micronutrients intake were collected from the patients' medical files, and some missing data were collected by phone directly from the patients. Results: The results of the linear regression showed that only age was significantly and positively (ß = 0.454; P = 0.001) associated with severity of the disease among the study patients. Approximately 57% of the COVID-19 patients consumed 3 meals daily, while 31-34% consumed 1 to 2 snacks daily. The majority (64%) of the patients drank more than 5 cups of water daily. Around 24% of the patients complained of eating problems, such as taste and/or smell loss, low appetite, and swallowing difficulty. The intakes of the vitamins B1, B2, B3, B6, and C, as well as calcium, magnesium, phosphorus, selenium, and sodium, were within the recommended dietary allowances (RDA). Conclusion: The servings of the 5 food groups as well as most of the macro- and micronutrient requirements were within the recommended intakes and RDA.